On an accelerated procedure of extrapolation. (1981) - Yeyios, A.
Abstract : This paper presents some theoretical results concerning an extrapolation method, based on a completely consistent linear stationary iterative method of first degree, for the numerical solution of the linear systemA u = b .The main purpose of the paper is to find ranges for the extrapolation parameter, such that the extrapolation method converges independently of whether the original iterative method is convergent or not.